KAJIAN TINDAK TUTURI ILOKUSI DALAM PODCAST MATA NAJWA EPISODE “KISAH DARI POSKO PENGUNGSIAN BANJIR ACEH” - Nadya Puspa, Desilva; Sahidin, Didin; Ninah Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the forms, functions, and contexts of illocutionary speech acts found in the Mata Najwa podcast episode entitled Kisah dari PoskoPengungsian Banjir Aceh. This study used a descriptive qualitative method with a pragmatic approach. According to Searle (1979), illocutionary speech acts consist of assertive, directive, expressive, commissive, and declarative, acts. The result indicatethat assertive and eskpresive speech acts are the dominat forms found in the podcast. The speech acts function to provide information, express emotions, criticize social conditions, and build public empathy toward flood victims The findings also show that digital media such as podcasts have an important role in shaping social awareness and humanitarian solidarity.